2016
DOI: 10.1177/1932296816680632
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Model Predictive Control for the Artificial Pancreas Using a Confidence Index Based on Residual Analysis of Past Predictions

Abstract: Background: Model predictive control (MPC) performance depends on the accuracy of the prediction model implemented by the controller. Complex physiology and modeling limitations often prevent the ability to provide long and accurate glucose predictions, which results in the need to account for prediction errors. Method:Optimal insulin dosage by Zone-MPC is calculated by solving an optimization problem in which a scalar index is minimized by penalizing relative input deviations and glucose predictions out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The baseline zone-MPC design, aimed to succeed in non-pregnancy glucose target range of 70 – 180 mg/dL, showed a performance above 95% time in this range for all but extreme case scenarios explored in this study. The high percentage of time in the non-pregnancy target range obtained by the baseline zone-MPC is consistent with some of the previous in-silico studies on zone-MPC ( 40 , 41 ) Both studies reported above 90% time in 70 - 180 mg/dL while the meals in their scenarios had higher carbohydrate content (i.e., ranging from 50 to 100 grams per meal) compared to our experiments (i.e., 40 grams per meal). In our work, low carbohydrate content of the meals, all meals being announced at or before their intake and accurately, the effect of titrating the insulin treatment parameters to achieve pregnancy-specific glucose control requirements in Scenario A and partially in Scenario C contributed to the high performance of all three controllers.…”
Section: Discussionsupporting
confidence: 90%
“…The baseline zone-MPC design, aimed to succeed in non-pregnancy glucose target range of 70 – 180 mg/dL, showed a performance above 95% time in this range for all but extreme case scenarios explored in this study. The high percentage of time in the non-pregnancy target range obtained by the baseline zone-MPC is consistent with some of the previous in-silico studies on zone-MPC ( 40 , 41 ) Both studies reported above 90% time in 70 - 180 mg/dL while the meals in their scenarios had higher carbohydrate content (i.e., ranging from 50 to 100 grams per meal) compared to our experiments (i.e., 40 grams per meal). In our work, low carbohydrate content of the meals, all meals being announced at or before their intake and accurately, the effect of titrating the insulin treatment parameters to achieve pregnancy-specific glucose control requirements in Scenario A and partially in Scenario C contributed to the high performance of all three controllers.…”
Section: Discussionsupporting
confidence: 90%
“…Spurred by these successes more extensive, long-term trials are planned. In work parallel to that presented in this paper the authors are investigating more extensive personalization (Pinsker et al 2016, Lee, Dassau, Gondhalekar, Seborg, Pinsker & Doyle III 2016), control-oriented models more elaborate than LTI (Colmegna, Sánchez-Peña, Gondhalekar, Dassau & Doyle III 2016 a , b , Colmegna, Sánchez-Peña & Gondhalekar 2016), enhanced cost functions (Lee, Gondhalekar, Dassau & Doyle III 2016, Rebello et al 2017), and real-time adaptation of the control strategy (Laguna Sanz et al 2016, Cao et al 2017). Planned future work focuses on the design of control laws for people that exercise, for a wider range of users, e.g., young children and people with disorders in addition to T1DM, and exploiting non-BG feedback by, e.g., activity trackers.…”
Section: Discussionmentioning
confidence: 92%
“…[ 11 12 ] However, BGC control methods, particularly MPC, require the prediction of BGC. [ 13 14 ] Thus, it is essential to develop a model that can predict BGC. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%